Household Solid Waste Management in Communities Living in Plantation Areas - Hasanah, Swara Mega (Insights in Public Health Journal, 2025)
Background: The cause of the lack of waste management in the community in the plantation area is the lack of sanitation facilities in the community. environmental health risks are associated with households that do not utilize waste services or possess trash bins. This study aims to determine the condition of household solid waste processing in the community in the plantation area in Banjarsari Village, Bangsalsari District, Jember Regency. Methods: The research design employed is descriptive research. Descriptive research methods are employed to address issue formulations in research concerning the treatment of household solid waste. Results: The result of this study shows that 94.12% or 32 respondents who have their own trash cans and the rest do not have trash cans. For 2 respondents with a percentage of 5.88% do not have their own trash cans. All respondents processed waste by burning, namely 34 (100%) respondents. There are no TPS in the plantation area Conclusions: The Banjarsari plantation does not have a temporary Waste Storage (TWS), resulting in the community processing waste by burning. Processing waste by burning can have negative effects on the environment and health